2014
DOI: 10.1179/1743284714y.0000000545
|View full text |Cite
|
Sign up to set email alerts
|

Spheroidisation of hypereutectoid state of nanostructured bainitic steel

Abstract: Nanostructured bainite is extremely resistant to severe tempering making it difficult to reduce its hardness sufficiently to allow certain processing before heat treatment into its final state. An attempt is therefore made to introduce the divorced pearlite reaction that relies on the presence of pro-eutectoid cementite in the austenite in order to produce a microstructure containing spheroidal cementite particles simply by continuous cooling from the two phase austenite and cementite field. It is demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…A careful examination of the tielines operating during growth showed that at low temperatures, there is very little partitioning of manganese between the phases and partitioning becomes prominent for transformation at temperatures near the eutectoid ( Table 1). The extent of partitioning is predicted well using our mixed diffusion model, when compared against the microanalytical data of Hutchinson et al 21 for Fe-3?50Mn-2?46C (at-%) steel at 898 K, 21 Fig. 6.…”
Section: Mixed Diffusion Controlled Growth For Fe-mn-cmentioning
confidence: 92%
“…A careful examination of the tielines operating during growth showed that at low temperatures, there is very little partitioning of manganese between the phases and partitioning becomes prominent for transformation at temperatures near the eutectoid ( Table 1). The extent of partitioning is predicted well using our mixed diffusion model, when compared against the microanalytical data of Hutchinson et al 21 for Fe-3?50Mn-2?46C (at-%) steel at 898 K, 21 Fig. 6.…”
Section: Mixed Diffusion Controlled Growth For Fe-mn-cmentioning
confidence: 92%
“…However, heat treatments can be designed so that the proeutectoid cementite need not be present in the final microstructure. 55 Indeed, carbide-free structures are now being investigated for low alloy bearing steels; 51,55 more expensive steels containing a large solute content, such as the Cronidur 30, 56,57 are already available for specialist aerospace applications, with a low carbon concentration that avoids carbides that are undissolved at the austenitisation temperature.…”
Section: Hypothesis and Solutionsmentioning
confidence: 99%
“…Softening may also be necessary to allow thermo-mechanical processing. [10,11] Previous work has shown that these steels are relatively resilient to tempering. [1,8,12] The fine plate size provides the dominant strength contribution, so high hardness is maintained until coarsening of the bainitic ferrite occurs.…”
Section: Introductionmentioning
confidence: 99%